Militer Pada Pemilu Legislatif : Antara Netralitas dan Profesionalitas - Yanuar, Deni (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2017)
This paper wants to review the findings of the Indonesian National Army in the legislative elections, which post the abolition of the Indonesian military's dual function policy. The argument in this paper that the professionalism of the TNI is one of the supporting factors in realizing a clean democracy by maintaining security in the legislative elections in Bireun Regency. It is seen from several things. First, the security carried out by the TNI during the legislative elections. Second, discipline members and families from being involved in legislative elections. This study uses a qualitative research approach that is able to generate descriptive data related to the role of the TNI in legislative elections. The results of this study show that there is a professional TNI in maintaining security during the legislative election process while remaining consistent with its neutrality policy. Thus the role of the community is still very necessary in providing support to the consistency of TNI neutrality and professionalism so as to affect the maturity of electoral democracy.